Infection of an Individual with Plague in the Gorno-Altaisk High-Mountain Natural Focus in 2014. Communication 1. Epidemiological and Epizootiological Peculiarities of Plague Manifestations in the Gorno-Altaisk High-Mountain (Sailyugemsky) Natural Plague Focus - V. V. Kutyrev; A. Yu. Popova; E. B. Ezhlova; Yu. V. Demina; N. D. Pakskina; L. V. Shchuchinov; E. P. Mikhailov; A. I. Mishchenko; E. N. Rozhdestvensky; G. Kh. Bazarova; A. V. Denisov; I. N. Sharova; et al. (Проблемы особо опасных инфекций, 2014)
For the first time ever since the discovery of the Gorno-Altaisk high-mountain natural focus in 1961, registered has been a case of human plague infection. It occurred in the consequence of the grey marmot cutting that was caught in the territory of one of the persistent epizootic regions of the natural plague focus. The outbreak was localized and eliminated following complex anti-epidemic measures, including medical treatment of the patient; identification, isolation and management of the contact persons, both to the patient and marmot; withdrawal and disposal of marmots’ carcasses, obtained during unauthorized commercial hunting; specific and non-specific prophylaxis of the disease. Also for the first time ever received have been the evidences of concurrent circulation of the strains, subspecies Y. pestis ssp pestis and Y. pestis ssp. altaica in the regions of cohabitation of Pallas’ pika (Ochotona pallasi), Siberian souslik (Citellus undulatus), and grey marmot. Specified is the necessity to reconsider the tactics of epizootiological plague monitoring in enzootic territories where circulation of various Y. pestis subspecies is registered.